2017
DOI: 10.1515/pjfns-2016-0032
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Biological Properties of Agaricus bisporus Fruiting Bodies- a Review

Abstract: White Agaricus bisporus is both the most popular and the most commonly eaten edible mushroom species in the world. It is popular not only because of its taste, but also due to its high level of nutrients: dietary fi ber (chitin), essential, semi-essential amino acids, unsaturated fatty acids including linoleic and linolenic acids, easily digestible proteins, sterols, phenolic and indole compounds, and vitamins − especially provitamin D 2 and B 1 , B 2 , B 6 , B 7 , and C. Fruiting bodies of A. bisporus have an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 53 publications
5
62
0
1
Order By: Relevance
“…Alispahić et al (2015) found that total phenolic content in fresh fruiting bodies of A. bisporus was 6.43 mg GAE/g of fresh mushrooms. According to Palacios et al (2011) and Muszyńska et al (2017) A. bisporus fruiting bodies contain total phenolic compunds level of 3.5 mg GAE/g of dry mushrooms and individual phenolics such as caffeic, chlorogenic, p-coumaric, ferulic, gallic, p-hydroxybenzoic, homogenistic, protocatechuic acids and catechin, myricetin and pyrogallol too, which may be pottentially polymerized into melanin.…”
Section: Resultsmentioning
confidence: 99%
“…Alispahić et al (2015) found that total phenolic content in fresh fruiting bodies of A. bisporus was 6.43 mg GAE/g of fresh mushrooms. According to Palacios et al (2011) and Muszyńska et al (2017) A. bisporus fruiting bodies contain total phenolic compunds level of 3.5 mg GAE/g of dry mushrooms and individual phenolics such as caffeic, chlorogenic, p-coumaric, ferulic, gallic, p-hydroxybenzoic, homogenistic, protocatechuic acids and catechin, myricetin and pyrogallol too, which may be pottentially polymerized into melanin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, gene-protecting activity of this species was studied, which was a result of the presence of tyrosinase. Such protective effect may be related to the pathway of transformation of tyrosine into l-DOPA (l-3,4-dihydroxyphenylalanine), and further conversion into dopaquinone metabolite [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Agaricus bisporus (Ab; champignon) and Pleurotus ostreatus (Po; oyster mushroom) are two species dominating mushroom cultivation worldwide and have been widely studied (Roncero-Ramos & Delgado-Andrade, 2017). The popularity of A. bisporus is not only because of its taste and aroma, but also because of the dietetic and medicinal properties due to the metabolite composition and biologically active elements such as dietary fiber, essential amino acids and antioxidant substances, unsaturated fatty acids and vitamins (Muszyńska, Kała, Rojowski, Grzywacz, & Opoka, 2017). Also, the cultivation of P. ostreatus has been growing because of its short-life cycle with low demand for resources and technology.…”
mentioning
confidence: 99%